STMO-18 SUBPIAL RESECTION OF GLIOMA USING CUSA CLARITY. (16th December 2019) - Saito, Kuniaki; Kobayashi, Keiichi; Iijima, Shohei; Matsumoto, Yoshie; Shimada, Daisuke; Shiokawa, Yoshiaki; Nagane, Motoo
Abstract: BACKGROUND: Maximum safe resection is a primary goal of glioma surgery. Ultrasonic aspiration is commonly used technique in neurosurgery, as it allows for safely debulking of tumors without damaging the adjacent brain tissue. CUSA Clarity helps to avoid damage to blood vessels and nerve fibers due to its original function, 'Tissue Select'. Here we introduce glioma surgery using CUSA Clarity. METHODS: We used CUSA Clarity in three cases with glioma at Kyorin University Hospital. According to fragility of the tissues and hardness of the tumor, we adjusted power, irrigation, and Tissue Select level of CUSA Clarity. We also introduce subpial aspiration technique in glioma surgery using normal CUSA. RESULTS: Histological diagnoses of the three patients were WHO grade IV glioblastoma, grade III anaplastic astrocytoma, and grade II oligodendroglioma. All patients underwent successful maximum safe resection without ischemic complication. CUSA Clarity allowed for safe subpial dissection and preservation of pia and small vessels more perfectly than surgery using normal CUSA. CUSA Clarity also contributed to bloodless dissection of the tumor margin due to avoidance of feeder injury. When using Tissue Select mode, the power of the CUSA was elevated by 10 or 20 to aspirate the tumor effectively. CONCLUSION: CUSA Clarity contributes to safe resection of glioma due to selective tumor aspiration by Tissue Select.